Radiation resistance of normal human astrocytes: the role of non-homologous end joining DNA repair activity. (13th November 2018) - Bylicky, Michelle A; Mueller, Gregory P; Day, Regina M
Abstract: Radiotherapy is a common modality for treatment of brain cancers, but it can induce long-term physiological and cognitive deficits. The responses of normal human brain cells to radiation is not well understood. Astrocytes have been shown to have a variety of protective mechanisms against oxidative stress and have been shown to protect neurons. We investigated the response of cultured normal human astrocytes (NHAs) to X-ray irradiation. Following exposure to 10 Gy X-irradiation, NHAs exhibited DNA damage as indicated by the formation of γ-H2AX foci. Western blotting showed that NHAs displayed a robust increase in expression of non-homologous end joining DNA repair enzymes within 15 min post-irradiation and increased expression of homologous recombination DNA repair enzymes ~2 h post-irradiation. The cell cycle checkpoint protein p21/waf1 was upregulated from 6–24 h, and then returned to baseline. Levels of DNA repair enzymes returned to basal ~48 h post-irradiation. NHAs re-entered the cell cycle and proliferation was observed at 6 days. In contrast, normal human mesenchymal stem cells (MSCs) failed to upregulate DNA repair enzymes and instead displayed sustained upregulation of p21/waf1, a cell cycle checkpoint marker for senescence. Ectopic overexpression of Ku70 was sufficient to protect MSCs from sustained upregulation of p21/waf1 induced by 10 Gy X-rays. These findings suggest that increased expression of Ku70 may be a key mechanism for the radioresistance of NHAs, preventing their accelerated senescence from high-dose radiation. These results may have implications for the development of novel targets for radiation countermeasure development.